النظرية السلوكية في تعليم المحادثة: BEHAVIORAL THEORY IN CONVERSATION TEACHING - Nur'ainun Ritonga (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: This research aims to describe the concept of behavioral theory and its application in conversation education. This research will answer the questions: (1) What is the concept of behavioral theory, (2) How it is applied in teaching conversation. This research was done on the qualitative entrance to the desk study. The research result is: (1) Behavioral theory is the theory of behavior development measured and observed that results from responding to students' incentives. And the advantages of behavioral theory are accustoming the teacher to be sensitive to study cases and it is appropriate to obtain the ability that needs to be applied and repeated, such as speed, reflection, suffering and others. (2) Developing the ability to start speaking to learners without waiting for the development of their linguistic wealth and the ability to accomplish, developing the ability of learners to innovate and act on different situations, choosing the most appropriate responses and distinguishing between valid alternatives in each situation, exposing learners to different situations, translating the communicative concept of language and training the student to communicate Actively with Arabic speakers and encourage the student to speak a language other than his own in front of his colleagues. الكلمات الأساسية : النظرية السلوكية، تعليم المحادثة